2013
DOI: 10.1155/2013/171437
|View full text |Cite
|
Sign up to set email alerts
|

TNF-αand IFN-s-Dependent Muscle Decay Is Linked to NF-κB- and STAT-1α-StimulatedAtrogin1andMuRF1Genes in C2C12 Myotubes

Abstract: TNF-α was shown to stimulate mitogenicity in C2C12 myoblasts. Selected cytokines TNF-α, IFNα, or IFNγ reduced the expression of myosin heavy chain (MyHC IIa) when given together. Molecular mechanisms of cytokine activities were controlled by NF-κB and JAK/STAT signaling pathways, as metabolic inhibitors, curcumin and AG490, inhibited some of TNF-α and IFNα/IFNγ effects. Insulin was hardly antagonistic to TNF-α- and IFNα/IFNγ-dependent decrease in MyHC IIa protein expression. Cytokines used individually or toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…In our previous paper [ 44 ] we showed that cytokine-induced muscle atrophy is mediated by NF-κB and STAT-1α which both cause upregulation of muscle-specific atrogenes (atrogin-1 and MuRF1) that can’t be prevented by insulin. Dehoux et al [ 45 ] also observed that IGF-1 could not overcome the catabolic effect induced by proinflammatory cytokines despite activation of Akt/FOXO and GSK-β pathways and inhibition of atrogin-1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous paper [ 44 ] we showed that cytokine-induced muscle atrophy is mediated by NF-κB and STAT-1α which both cause upregulation of muscle-specific atrogenes (atrogin-1 and MuRF1) that can’t be prevented by insulin. Dehoux et al [ 45 ] also observed that IGF-1 could not overcome the catabolic effect induced by proinflammatory cytokines despite activation of Akt/FOXO and GSK-β pathways and inhibition of atrogin-1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Akt also phosphorylates and inhibits the Forkhead box O (FOXO) family of transcription factors, thereby repressing their transcriptional activation of the E3 ubiquitin ligases Muscle Atrophy Fbox (MAFbx) (also known as atrogin‐1) and Muscle Ring Finger 1 (MuRF1) which function to promote ubiquitination and subsequent proteasomal degradation of target substrates . Pro‐inflammatory cytokines such as tumour necrosis factor alpha (TNF‐α) can also act to induce atrophic genes such as MuRF1 and atrogin‐1/MAFbx by activating the nuclear factor‐kappa B (NF‐kB) family of transcription factors . Therefore, a number of distinct signalling pathways have been implicated in controlling skeletal muscle hypertrophy and atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…9 Pro-inflammatory cytokines such as tumour necrosis factor alpha (TNF-α) can also act to induce atrophic genes such as MuRF1 and atrogin-1/MAFbx by activating the nuclear factor-kappa B (NF-kB) family of transcription factors. 26 Therefore, a number of distinct signalling pathways have been implicated in controlling skeletal muscle hypertrophy and atrophy. Notably, diet-induced obesity or short-term high fat feeding has been shown to promote or augment muscle atrophy and catabolism, as evidenced by reduced muscle mass and muscle fibre size, in association with up-regulated expression of atrophic factors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…TNF has been reported to trigger muscle catabolism through the NF-κB transcription factor (32), which rapidly enhances the transcription of E3 ubiquitin ligases, such as atrogin-1/MAFbx and MuRF1, and increases the levels of free ubiquitin, which in turn potently mediate the degradation of muscle contractile proteins (23,27,33,34). By contrast, the results of the current study demonstrate that TNF increases VHL expression through a mechanism which is transcriptionindependent, involving the enhanced translation/stabilization of the VHL protein.…”
Section: Discussionmentioning
confidence: 99%